IMPROVING THE LEGISLATION OF THE REPUBLIC OF UZBEKISTAN IN TERMS OF CRIMES AGAINST PEACE AND SECURITY OF MANKIND (American Journal of Interdisciplinary Research and Development, 2023)
There is little doubt that crimes against peace and security of mankind are considered as heinous offences due to the fact that peace as well as security of mankind are conceived as pivotal objects of the criminal law. The authorities are persistently required to improve the legal system pertaining to this field. Thus, this article is devoted to matters of enhancing the legal norms in terms of this field.